(3OQGSI ebGQfIs - (3MGRe eMehO YjSi(B, (3GdhGOjs ((3GQHO(B:s (3YGde GdcJGH GdMOjK(B,s, 2009)
(3JYQja GdcaGAI , GdSjGSI GdfbOjI GdJbdjOjI h GdSjGSI GdfbOjI GdGSdGejI , GdfXGe GdfbOj GdJbdjOj h GdeUQa GdeQcRj GdJbdjOj , EOGQI cejI GdfbhO h GdSjGSI GdfbOjI GdJbdjOjI , GdfXGe GdfbOj GdGSdGej , YdGbI ebGUO GdTQjYI GdGSdGejI HGdehGQO GdeGdjI , GdeUQa GdeQcRj GdGSdGej , EOGQI GdfbO GdGSdGej ,CgOGa h COhGJ GdSjGSI GdfbOjI GdGSdGejI ,CKQ caGAI GdSjGSI GdfbOjI GdJbdjOjI GdCQOfjI h GdSjGSI GdfbOjI GdGSdGejI GdShOGfjI , ebGQfI CKQ GdSjGSI GdfbOjI GdGSdGejI HGdJbdjOjIs
(3agQS GdLOGhd U(B.7s
Keywords: (3GdGbJUGO GdGSdGejs; (3GdHfhc GdGSdGejIs; (3GdSjGSI GdfbOjIs; (3GdfbhOs